2021
DOI: 10.3389/fneur.2021.578324
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic Local Field Potentials Are Related to Long-Term DBS Effects in Tourette Syndrome

Abstract: Background: Local field potential (LFP) recordings helped to clarify the pathophysiology of Tourette syndrome (TS) and to define new strategies for deep brain stimulation (DBS) treatment for refractory TS, based on the delivery of stimulation in accordance with changes in the electrical activity of the DBS target area. However, there is little evidence on the relationship between LFP pattern and DBS outcomes in TS.Objective: To investigate the relationship between LFP oscillations and DBS effects on tics and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The search for tic-related neurophysiological markers and their distinguishing features from voluntary actions has been further augmented by the therapeutic application of deep brain stimulation in tic disorders, as it provided a means to record neurophysiological signals from subcortical structures. Several studies by now have demonstrated that a low-frequency oscillatory signal (between 3 and 12 Hz) recorded from both thalamic (typically from the centromedian–parafascicular nucleus CM-Pf/ in proximity to the nucleus ventralis oralis internus, Voi) and pallidal (globus pallidus pars interna) structures correlates with tic severity measures,( Bour et al, 2015 , Cagle et al, 2020 , Jimenez-Shahed et al, 2016 , Marceglia et al, 2021 , Marceglia et al, 2010 , Neumann et al, 2018 , Shute et al, 2016 ). Importantly, one study demonstrated that the duration rather than the amplitude of theta burst activity by both structures was associated with preoperative tic severity ( Neumann et al, 2018 ).…”
Section: Ticsmentioning
confidence: 99%
“…The search for tic-related neurophysiological markers and their distinguishing features from voluntary actions has been further augmented by the therapeutic application of deep brain stimulation in tic disorders, as it provided a means to record neurophysiological signals from subcortical structures. Several studies by now have demonstrated that a low-frequency oscillatory signal (between 3 and 12 Hz) recorded from both thalamic (typically from the centromedian–parafascicular nucleus CM-Pf/ in proximity to the nucleus ventralis oralis internus, Voi) and pallidal (globus pallidus pars interna) structures correlates with tic severity measures,( Bour et al, 2015 , Cagle et al, 2020 , Jimenez-Shahed et al, 2016 , Marceglia et al, 2021 , Marceglia et al, 2010 , Neumann et al, 2018 , Shute et al, 2016 ). Importantly, one study demonstrated that the duration rather than the amplitude of theta burst activity by both structures was associated with preoperative tic severity ( Neumann et al, 2018 ).…”
Section: Ticsmentioning
confidence: 99%
“…Local field potentials can be recorded during deep brain stimulation (DBS) implantation surgery. A retrospective clinical study of 17 patients with TS who underwent DBS of the thalamus showed that increased power in the low-frequency (5–15 Hz) band could be a biomarker for TS and correlated with the severity of tics 42 .…”
Section: Pathophysiologymentioning
confidence: 99%